EFFECT OF SYSTEMIC AND INTRAUTERINE ADMINISTRATION OF DRUG ON ENDOMETRITIS IN COW - MAHTO, DINESH; SINHA, M P; SINGH, BALRAJ; JHA, D K (The Indian Journal of Animal Reproduction, 2023)
A total of 18 selected cows with endometritis were randomly allocated to 3 groups, comprising of 6 animals in each group. Ceftriaxone sodium at a dose rate of 10 mg/kg body weight was administered only once through I.V., 1.M. and I.U. routes to each of 6 animals in different groups. Efficacy of the treatment of endometritis with Ceftriaxone was judged on the basis of bacteriological record. The average bacterial colonies count recorded was 247.66 X 106 /ml of uterine fluid before treatment in all groups. The mean bacterial colony counts per ml of uterine fluid decreased to the minimum (4.00 ± 0.36 X 106 /ml) 3 hours after I.V, 1 hour (5.33±0.55 X 106 /ml) after 1.U and 6 hours (5.33±0.66 X 106 /ml) after I.M. administration of drug and again increased gradually reaching to 56.66 ±1.80 X106 /ml, 85.33 ±2.78 X106 /ml and 81.16 ± 1.24 X106 /ml of uterine fluid , respectively at 72 hours. The estrual discharge was mucopurulent before treatment & became clear after treatment. Before treatment all the endometritic cows were positive to white side test which became negative post treatment.